Perfil imuno-histoquímico e estado físico genômico do Papilomavírus humano (HPV) em tumores de pênis - TEIXEIRA JÚNIOR, Antonio Augusto Lima (2019)
Penile cancer is considered a rare cancer in developed countries. However, it has a high incidence in developing countries, such as Africa, Asia and South America. The state of Maranhão, Brazil, has the highest global incidence ever recorded, being considered a serious local public health problem. Despite being associated with some risk factors, such as human papillomavirus (HPV) infection, there are still few studies that aim to understand the biology of these tumors, especially with diagnostic, prognostic and therapeutic findings. Therefore, this study aimed to identify the genomic physical state of human papillomavirus (HPV) in penile tumors and to evaluate the expression profile of ki67, p53, p16 and E6 proteins. The survey of cases diagnosed in two referral hospitals in Maranhão (HUUFMA and HCAB) was carried out, from which 100 cases were submitted to the analyzes proposed in this study. All cases were histologically reviewed by two distinct pathologists. HPV detection was conducted by qualitative PCR from biological material (DNA) obtained from paraffin blocks containing tumor tissue from each patient using the generic primers PGMY09 / 11 and GP5 + / GP6 +. Amplicons were evaluated on 1.5% agarose gel. Protein expression analysis was conducted by immunohistochemistry using monoclonal antibodies for each marker and following the manufacturer's recommendations. The HPV physical state was evaluated by the HPV-IntG / PCR multiplex (in house) method and was classified as episomal, integrated or mixed. The results of this research revealed a high prevalence of human papillomavirus (HPV) infected tumors, with 67.1% of the positive cases in molecular analysis (PCR). It was possible to evaluate the HPV genomic physical state in 11 samples, all of which had viral integration in the host genome, with a more prevalent integration pattern involving the E1 and E7 regions of the viral genome (54.5%). When histologically evaluated, 88.4% of the cases presented alterations suggestive of virus infection (koilocytosis) and 58% presented overexpression of p16 protein, an indirect marker of high oncogenic risk HPV infection. Positivity for p16 was associated with the presence of HPV by PCR (p=0.006), HPV-associated histological subtypes (p=0.05), and basaloid histological subtype (p=0.02). Absence of E6 expression was associated with well-differentiated (p=0.001) tumors, absence of angiolymphatic (p=0.001) and perineural (p=0.001) invasion, staging I-II (p = 0.01) and condylomatous tumors (p = 0.005). While positivity for E6 was associated with lymph node metastasis (p=0.001) and extranodal extension (p = 0.02). About 64% of the cases were negative in p53 expression analysis, which was associated with clinical and histopathological characteristics such as: histological subtype (p=0.002), degree of differentiation (p=0.007) and primary tumor (p=0.02). The ki67 expression profile also showed association with important parameters such as lesion size (p= 0.04), degree of differentiation (p=0.001), perineural invasion (p=0.05), staging (p=0,03), lymph node metastasis (p=0.002) and extranodal extension (p=0.002). In the analysis of disease-free survival (SLD), the presence of koilocytosis and negativity for p53 were associated with better SLD, while positivity for p16 and E6 was associated with lower disease-free survival. The findings of this research corroborate other studies that show a high prevalence of HPV-infected penile tumors in Maranhão and describe for the first time the profile of viral genome integration in penile tumors in an area with high incidence of penile cancer. In addition, it reveals a protein expression profile with important associations with diagnostic and prognostic factors.